Penetration testing with paspberry Pi : construct a hacking arsenal for penetration testers or hacking enthusiasts using Kali Linux on a Raspberry Pi /: construct a hacking arsenal for penetration testers or hacking enthusiasts using Kali Linux on a Raspberry Pi. (2015) - Lakhani, Aamir; Muniz, Joseph
No abstract available